Analisis Dampak Toko Modern Terhadap Keberadaan Usaha Mikro, Kecil, Menengah Di Kota Padangsidimpuan - Kurniawan, Rahmat (AT-TAWASSUTH: Jurnal Ekonomi Syariah, 2019)
This research is to find out the perceptions of micro, small and medium enterprises to modern stores, MSME partnerships with modern stores, constraints, and the role of the government in overcoming the problems of modern shops and MSMEs in Padangsidimpuan City. This research is a descriptive qualitative study by conducting in-depth interviews. The results showed the perception of MSMEs towards modern stores had a negative and positive impact. The negative impact, the income of MSMEs has decreased. The positive impact, the presence of modern stores motivates MSMEs to evaluate themselves from modern stores. The partnership established by MSMEs with modern stores is the use of business locations provided by modern stores. The constraints of MSMEs are business capital, human resources, business legality, business permits and products, while the constraints of modern stores are business permits, human resources and partnerships with MSMEs. The role of the City Government of Padangsidimpuan is for modern stores, namely to give an appeal not to add to modern store outlets and to call for partnerships in terms of marketing local MSME products. For MSMEs, facilitate MSMEs with banking institutions in terms of providing venture capital, training and guidance to MSMEs, and making packaging houses.This research is to find out the perceptions of micro, small and medium enterprises to modern stores, MSME partnerships with modern stores, constraints, and the role of the government in overcoming the problems of modern shops and MSMEs in Padangsidimpuan City. This research is a descriptive qualitative study by conducting in-depth interviews. The results showed the perception of MSMEs towards modern stores had a negative and positive impact. The negative impact, the income of MSMEs has decreased. The positive impact, the presence of modern stores motivates MSMEs to evaluate themselves from modern stores. The partnership established by MSMEs with modern stores is the use of business locations provided by modern stores. The constraints of MSMEs are business capital, human resources, business legality, business permits and products, while the constraints of modern stores are business permits, human resources and partnerships with MSMEs. The role of the City Government of Padangsidimpuan is for modern stores, namely to give an appeal not to add to modern store outlets and to call for partnerships in terms of marketing local MSME products. For MSMEs, facilitate MSMEs with banking institutions in terms of providing venture capital, training and guidance to MSMEs, and making packaging houses.